ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI SAWAH DI KECAMATAN SUNGAI MANDAU KABUPATEN SIAK PROVINSI RIAU - Muhamad Rico Ananda, Khairizal; Khairizal; Azharuddin M; Khairudin (UIR Press, 2024)
The primary objective of the national food policy is to achieve self-sufficiency in rice production, which involves implementing various strategies to boost output. This study seeks to examine the factors that affect lowland rice production. A survey method was employed for the research, conducted in the Sugai Mandau District of Siak Regency, Riau Province, between April 2022 and August 2022. A total of 34 farmers were selected as samples using random sampling techniques. The data analysis was both descriptive and involved qualitative and quantitative approaches, utilizing both primary and secondary data sources. The findings from the regression analysis indicate that all independent variables collectively and significantly influence the dependent variable. The t-test results revealed that factors such as planting area, labor, seeds, urea, phonska, KCL, pesticides, and gramophone significantly impacted rice production. However, the SP-36 fertilizer did not show a significant effect on rice production in the Sungai Mandau District of Siak Regency, Riau Province.